Measurement and analysis techniques for precise engineering and medical applications - Setan, Halim (2004)
Many applications (especially engineering and medical) require precise measurement, ranging from micron-level (i.e. mechanical engineering applications) to cm-level (civil engineering applications). To date, many precise measurement techniques are available, such as Laser Scanner/Tracker, Close Range Photogrammetry, Global Positioning System (GPS), Total Station, Coordinate Measuring Machine (CMM), etc. This paper describes the on-going research works related to measurement and analysis for precise engineering and medical applications. The engineering applications are divided into 2 modules: deformation analysis and industrial applications. The deformation analysis module comprises of software development (GPSAD2000, DEFORM99, DEFORM) for processing data (from GPS, total station, geodetic/geotechnical techniques) for deformation analysis, development of interface to commercial software (STARNET, TGO), the applications of APSWIN (commercial monitoring software), and inter-disciplinary research with civil engineers. The industrial applications module also involves software development, and uses commercial systems/software (VIVID910 Laser Scanner system, V-STARS photogrammetric system, AXYZ system with Precision Total Station/Electronic Theodolite, PHOTOMODELER photogrammetric software, RHINOCEROS 3D modeling software) for inter-disciplinary research with mechanical engineers. The medical application module concentrates on the development of system/software for inter-disciplinary craniofacial applications (UTM, SIRIM, USM) and uses various systems/software (VIVID910 Laser Scanner system, DVD photogrammetric software, AUSTRALIS photogrammetric software, RAPIDFORM 3D modeling software). All the above research works also involve verification tests with other techniques/software (such as CMM system and STARNET software). The research findings to date show the importance of inter-disciplinary research works for both engineering and medical applications.